2019
DOI: 10.3892/etm.2019.7283
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow stem cell therapy for patients undergoing coronary artery bypass grafting: A meta‑analysis of 14 randomized controlled trials

Abstract: Autologous bone marrow stem cell (BMSC) therapy is a novel option for regenerative therapy in patients with ischemic heart disease. The aim of the present meta-analysis was to evaluate the effectiveness of BMSCs combined with coronary artery bypass grafting (CABG). The PubMed, Cochrane Library, EMBASE and Web of Science databases were searched from inception to November 22, 2017 for randomized controlled trials on BMSC therapy combined with CABG. Finally, 14 trials with a total of 596 participants were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…LVESV change and LVEDV change decreased in the BMSC group, but the difference was not statistically significant compared with the CABG group. Our meta-analysis demonstrated that there was a statistical difference in LVEDVI change (MD = −10.57 ml/m 2 ; 95% CI: −19.86 to −1.28 ml/m 2 ; P = 0.03) and LVESVI change (MD = −9.49 ml/m 2 ; 95% CI: −16.95 to −2.03 ml/m 2 ; P = 0.01) between the BMSC and CABG groups, while the meta-analysis of Wu et al [ 1 ] with 14 RCTs revealed no statistically difference between two groups. These indexes are more reflective regarding the heart function compared with LVEDV and LVESV, as each individual's body surface area is different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LVESV change and LVEDV change decreased in the BMSC group, but the difference was not statistically significant compared with the CABG group. Our meta-analysis demonstrated that there was a statistical difference in LVEDVI change (MD = −10.57 ml/m 2 ; 95% CI: −19.86 to −1.28 ml/m 2 ; P = 0.03) and LVESVI change (MD = −9.49 ml/m 2 ; 95% CI: −16.95 to −2.03 ml/m 2 ; P = 0.01) between the BMSC and CABG groups, while the meta-analysis of Wu et al [ 1 ] with 14 RCTs revealed no statistically difference between two groups. These indexes are more reflective regarding the heart function compared with LVEDV and LVESV, as each individual's body surface area is different.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic heart disease (IHD) remains one of the leading causes of morbidity and mortality worldwide, imposing both economic and healthy burdens on either developed and developing countries [ 1 3 ]. Myocardial ischemia often results in irreversible loss of viable myocardium and replacement by noncontractile scar tissue, leading to the impairment of left ventricular and cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although similar, it has to be noted that MSCs derived from different sources differ in terms of surface markers expression, proliferation and differentiation potential, clonality and paracrine activities (Markov et al., 2021 ). This approach has demonstrated positive outcomes for ischemic heart disease treatment, with low risk of rejection, and revascularization through temporal secretion of trophic, immunomodulatory, and pro‐angiogenic molecules (Wu et al., 2019 ). However, current treatments used for repairing damaged tissue, that are based on the application of stem cells, in particular MSCs, have struggled with respect to reproducible cell delivery and therapeutic efficacy (Ayyat et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite outcome variability, recent randomised multicenter trials with large patient populations such as phase II IMPACT-CABG [ 2 ], phase III PERFECT [ 3 ] and phase II/III COMPARE CPM-RMI [ 4 ] reported significant improvement in left ventricle ejection fraction (LVEF) in CD133 + BMSC recipients compared to the placebo group (CABG only). Meta-analyses accumulating large patient cohorts in randomised controlled trials (RCTs) confirmed an overall improvement in LVEF in response to BMSC treatment [ 5 , 6 ]. Confoundingly, clinically relevant improvement of LV function as well as non-responsiveness were both reported in BMSC/CABG recipients and the placebo/CABG group.…”
mentioning
confidence: 99%